SHARING BEHAVIOR IN THE CONTEXT OF ALTRUISM AS A FORM OF STRATEGY FOR BUILDING EMPATHY AND SOLIDARITY - Suhardita, Kadek; Widana, I Wayan; Degeng, I Nyoman Sudana; Muslihati, Muslihati; Indreswari, Henny (Indonesian Journal of Educational Development (IJED), 2024)
Sharing behavior is a key in altruism that serves as a strategy to strengthen empathy and solidarity within the community (Guttman et al., 2016). This study investigates the relationship between sharing behavior and altruism, and its effects on the development of empathy in the community. The literature review shows that the act of sharing not only strengthens social relationships but also increases understanding between individuals (Chiu et al., 2006). When individuals engage in sharing, they tend to be more caring towards others, and create a more cooperative environment (Schor & Fitzmaurice, 2015). Sharing behavior also plays a role in strengthening group solidarity, building trust and support among community members. Studies show that communities with a strong culture of sharing are better able to face various social and economic challenges (Carleton & Hsiang, 2016). However, barriers such as stigma and mistrust can hinder participation in sharing. Therefore, it is important to design interventions that can overcome these barriers and raise awareness of the importance of sharing as a form of altruism. Thus, it can be said that sharing behavior has an important role in building empathy and solidarity, and requires collaboration from various sectors to create a more inclusive and empathetic society (Tomasello et al., 2005)